Drop Out Among Primary School Students: Reasons, Experience and Mitigating Mechanisms: In Case of Bench- Maji Zone Shey-Bench Wereda. - Hailu , Addisalem; Kassaw , Dessalegn; Wondimu, Biniam (Journal of Social Work Education and Practice, 2023)
This study was conducted to assess the causes, experience and Mitigating mechanism of school dropout among primary school students in Benchi-Maji zone Shey Bench Wereda. The study mainly attempted to answer research questions like the major reason that leads students’ to drop out, the experiences of dropouts while they were out of school and mitigating mechanism of school dropout. The study adopted a qualitative research approach, and non-probability sampling techniques were used to identify participants of the study. An in-depth interview and focus group discussions are utilized as the main tools of data collection. Interviews were conducted with key informants like homeroom teachers, principal’s parents, and students. Thirty-three (33) participants were involved in an interview, and three focus group discussion is comprising 10 participants in each group were conducted accordingly. Generally, data were collected from 63 purposively sampled participants. The researcher transcribed the notes taken while having an interview and FGD with children’s (students), teachers and parents. The transcription, which is written in the Amharic language was translated to English as accurately as possible and presented in a narrative way through thematic analysis. Poverty, the absence of motivation and interest, peer pressure and school-related difficulties were identified as the main cause of school dropout. With regard to the experience of dropouts, the majority of dropouts engaged in helping families, leave the area in search of jobs and create different work opportunities to deal with life. In addition working with financial aid organizations, GOs, NGOs, eliminating illiteracy of the society through awareness creation programs, developing a good interpersonal relationship with students, a participating community in educational programs are among major mechanisms identified by stakeholders as a mitigating mechanism of school dropout. Finally based on the findings, conclusions and recommendations were made.